2002
DOI: 10.1074/jbc.c200148200
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin 1 Is Required for Maturation and Cell Surface Accumulation of Nicastrin

Abstract: Proteolytic processing of amyloid precursor protein generates ␤-amyloid (A␤) peptides that are deposited in senile plaques in brains of aged individuals and patients with Alzheimer's disease. Presenilins (PS1 and PS2) facilitate the final step in A␤ production, the intramembranous ␥-secretase cleavage of amyloid precursor protein. Biochemical and pharmacological evidence support a catalytic or accessory role for PS1 in ␥-secretase cleavage, as well as a regulatory role in select membrane protein trafficking. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
187
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(222 citation statements)
references
References 30 publications
33
187
1
Order By: Relevance
“…Earlier studies have shown that nicastrin can be co-immunoprecipitated and co-localized with PS1 in a variety of cells/neurons [1,30,37,44,49,55]. Consistent with previous reports [3,12,27,28,29,53], we find that PS1 is distributed widely in the adult rat brain.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Earlier studies have shown that nicastrin can be co-immunoprecipitated and co-localized with PS1 in a variety of cells/neurons [1,30,37,44,49,55]. Consistent with previous reports [3,12,27,28,29,53], we find that PS1 is distributed widely in the adult rat brain.…”
Section: Discussionsupporting
confidence: 92%
“…The nicastrin and PS1 antisera used in the present study have been previously characterized [29,30,51]. The specificity of antisera is further confirmed by our immunoblotting experiment, which showed that nicastrin antiserum essentially reacted with one major band of approximately 120 kDa corresponding to the mature complex glycosylated forms of the protein in all brain regions examined.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations